2008
DOI: 10.3746/jkfn.2008.37.9.1174
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Physicochemical Components and Antioxidant Activity of Aged Garlic at Different Temperatures

Abstract: Garlics were aged at 60, 70, 80, and 90 o C for 1, 3 and 6 days. Samples were analyzed for physico-chemical components and antioxidant activities, such as DPPH scavenging activity and reducing power of hot water and ethanol extracts. The Hunter L, a and b values were significantly lower in sample aged at higher temperature and for longer time. In initiation of aging, the share force was the lowest in sample aged at 90 o C (85.70±1.44 kg/cm 2 ) and it increased for 6 days to 411.30±13.90 kg/cm 2 in aging. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 8 publications
4
8
0
3
Order By: Relevance
“…In addition, the pH of BG significantly decreased from 5.27 to 4.01 during thermal processing, compared with 6.29 for FG ( P <0.05). This result was in agreement with the report of Shin et al (13), which showed that the pH of BG decreased during thermal processing. The decrease in pH for heated garlic samples was, in part, associated with the production of browning compounds upon heat treatment during the BG manufacturing process (14).…”
Section: Resultssupporting
confidence: 94%
“…In addition, the pH of BG significantly decreased from 5.27 to 4.01 during thermal processing, compared with 6.29 for FG ( P <0.05). This result was in agreement with the report of Shin et al (13), which showed that the pH of BG decreased during thermal processing. The decrease in pH for heated garlic samples was, in part, associated with the production of browning compounds upon heat treatment during the BG manufacturing process (14).…”
Section: Resultssupporting
confidence: 94%
“…Garlic (Allium sativum L.) has been widely used for millennia not only for cooking but also in traditional medicine to treat a wide range of disorders (Corzo-Martínez, Corzo & Villamiel, 2007;Kimura, Tung, Pan, Su, Lai & Cheng, 2017;Santhosha, Jamuna & Prabhavathi, 2013;Shin, Choi, Chung, Kang & Sung, 2008a). Its medicinal benefits have also been extended to processed products such as dehydrated garlic, garlic oil macerate, aged garlic extract (Choi, Cha & Lee, 2014) and recently to black garlic (BG) which is an Asian product considered one of the fastest-growing health foods (Zhang, Lei, Liu, Gao Xu & Zhang, 2015;Kimura et al, 2017, Ryu, & Kang, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the sensory properties of BG, it has been sold in different forms such as a whole BG, puree, powder, extract or capsule. The popularity of BG is increasing in Europe and America as an ingredient in high-end cuisine (Kim, Jung, Kang, Chang, Hong & Suh, 2012a), the food industry, alcoholic beverages, candies, ice creams, jams (Kim, Son, Kim & Kim, 2008;Lee, Kim, Kang, Kim, Lee & Ryu, 2010;Shin et al, 2008a), sausages (Yoon, Shin & Kang, 2014), vinegar (Sim, Hwang, Kang, Kim & Shin, 2014), tofu (Sim, Hwang, Kang, Kim & Shin, 2014), white pan bread (Wang, Lee & Lee, 2013), jelly (Kim & Rho, 2011), pork ham (Yang, Shin, Kang & Sung, 2011) and yogurt bases (Shin, Kim, Kang, Yang & Sung, 2010). Also, due to its high antioxidant capacity, BG has been incorporated in cosmetic industry in shampoos, facial creams, body soap and skin protectors (Kim, Jung, Kang, Chang, Hong & Suh, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, it was reported that allicin is a major substance that decreases lipids level in the body [52]. Also, it was reported that the fresh garlic is heat-treated into red garlic and black garlic, the phenolic compounds level tend to elevate [36,45]. Therefore, the red garlic extract is believed to be improving the lipid profiles in the liver and heart tissues of obese rats.…”
Section: Alt and Ast Activitiesmentioning
confidence: 99%
“…This is reportedly attributable to melanoidins [35,36,46,49], which are the browning substance in aged heat-treated garlic. Also, black garlic is known to variable bioactivities such as antioxidant [45,46], improvement of cardiovascular complications of diabetes [42], decline of lipids accumulation in hypercholesterolemic rats [22]. It was demonstrated that S-allyl cysteine [10,20] and polyphenol compounds in garlic exert strong antioxidant effect [48].…”
Section: Introductionmentioning
confidence: 99%